Investigating Chinese In-service Teachers’ Concerns About Teaching Thinking Using the Concern-Based Adoption Model (CBAM) (Journal of Education and Development, 2024)
Teaching thinking has been the focus of the new round of key competencies-oriented K-12 education reform in China. Based on the Concerns-Based Adoption Model (CBAM), this study investigated Chinese in-service teachers’ concerns about teaching thinking and how demographic variables affected their concerns. A questionnaire modified from the Stages of Concerns (SoC-TT) was used to collect the data. Altogether, 382 in-service teachers from 28 cities in China participated in this study by filling out the online questionnaire voluntarily and anonymously. The results showed that: (1) The modified seven-stage SoC-TT instrument showed satisfactory reliability and validity in the context of teaching thinking in China. (2) Teachers showed higher self-concerns (Informational and Personal) and impact concerns (Consequence, Collaboration, and Refocusing) while their task concerns (Management) about teaching thinking were relatively low. (3) Except for the Consequence stage, their demographic variables significantly influenced teachers’ concerns at other stages. Implications for professional development for teaching thinking were discussed.